A Preliminary Survey of Game Developer’s Perception on Game Clone : Case Study: GameDevID - Dodick Zulaimi Sudirman; Wayan Suparta (Bina Nusantara University, 2020)
If a developer uses trademarked content from other game such as images and music, it will be illegal. But it is fine for the developer to copy the gameplay and make innovative changes to improve the game. This is a good practice that boosts innovation in the video game industry that relies on creativity. The problem is when a developer decided to use the legality to simply copy other works with no spirit of innovation. This act of legal plagiarism is called video game clone. We need to have a more understanding of Indonesia game developer’s perception toward game cloning and plagiarism. Based on the survey, it can be concluded that Indonesia game developer, in general, has no problem with the act of game cloning. Although, more effort and focus could be given to protecting both creators and consumers from the negative intent of using game clone legality